Speeches in world history - McIntire, Suzanne 1951-; Burns, William E. 1959- (Facts on File library of world history, 2009)
Speeches in World History is a compilation of 200 of the world's greatest speeches from all major civilizations and throughout history--arranged in chronological order. Each section of this comprehensive collection, roughly corresponding to the eras used in the national world history standards, begins with an introduction that outlines key events that occurred during this time period. The documents come with an introduction that places each speech in historical context--explaining why it was significant and what happened as a result--and provides key information on the orator. --from publisher description.